Fungsi dan Makna Mantra pada Ibu Hamil, Proses Persalinan, dan Sawan pada Bayi di Plumpang Kecamatan Plumpang Kabupaten Tuban - Fina Lailatul Fadhilah (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas PGRI Ronggolawe, 2024)
This article is a study of spells for pregnant women, the process of childbirth, and convulsions for babies in Plumpang Village, Plumpang District, Tuban Regency. The study was carried out with three variants of the spell which aims to get the form of the spell, its function and meaning. The method used in this study is a descriptive method which aims to describe what happened and how it should have been when the research took place using a holistic folklore approach. Based on the analysis carried out, it was found that the structure of the three mantras consists of certain patterns which indicate that what is prioritized in the mantra is the aim of smooth running during pregnancy until the delivery process and health for the baby and mother, each mantra addressed to God who Almighty. The function of this mantra is as an educational tool and as cultural validation. The meaning of the three mantras is as a human request to God for health, smoothness, and safety for pregnant women and babies.